2002
DOI: 10.1055/s-2002-20160
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Antegrade Blood Cardioplegia: Cold vs. Tepid

Abstract: Uninterrupted cardioplegia can be safely performed with cold normokalemic CABCP. In contrast, tepid normokalemic CABCP leads to fibrillation, jeopardizes the heart, and should be avoided.UND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This information demonstrates a better preservation of the myocardium with the spontaneous reestablishment of the coordinated heartbeat. 12,19,20 In summary, the present study demonstrates the physiological alterations that occur in the myocardium in acutely ischemic hearts submitted to reperfusion. The differences in the type of protection are clear in the two different strategies adopted for the protection of the myocardium.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This information demonstrates a better preservation of the myocardium with the spontaneous reestablishment of the coordinated heartbeat. 12,19,20 In summary, the present study demonstrates the physiological alterations that occur in the myocardium in acutely ischemic hearts submitted to reperfusion. The differences in the type of protection are clear in the two different strategies adopted for the protection of the myocardium.…”
Section: Discussionmentioning
confidence: 52%
“…The SG group presented a medium of zero defibrillations necessary to reestablish the coordinated heartbeats. This information demonstrates a better preservation of the myocardium with the spontaneous reestablishment of the coordinated heartbeat 12,19,20 …”
Section: Discussionmentioning
confidence: 84%
“…16 The main reason for using a lower temperature was based on previous studies that demonstrated the efficacy and cardioprotective effect of administration at low temperature. 17 These differences might explain the enhanced cardiac function and reduction in myocardial damage in comparison with the work of Aass and coworkers. 7 In addition, we investigated expression levels of miRNAs in LV tissue samples.…”
Section: Discussionmentioning
confidence: 93%
“…Baretti opens with the identical and widely used definition of Grammar given by Johnson: 'Grammar, which is the art of using words properly, comprises four parts, Orthography, Etymology, Syntax, and Prosody'. 48…”
Section: Baretti's Models and Competitorsmentioning
confidence: 99%